Modeling of cyclic hardening of metals coupled with martensitic transformation - Mróz, Z.; Ziętek, G. (Archives of Mechanics, 2007)
The work presents an elasto-plastic material model with mixed hardening taking into account martensitic transformation. Modification of the kinematic hardening rule is proposed by relating back stress to the generalized thermodynamic force by a nonlinear function dependent on the fraction of martensite. The martensitic evolution is expressed in terms of isotropic hardening parameter by introducing proper free energy related force. The proposed model has been applied to predict hysteretic response for cyclic tension and compression tests for austenitic steel.